THE ADMISSIBILITY OF EVIDENCE OBTAINED IN THE PROCESS OF ENSURING THE SAFETY OF PARTICIPANTS IN CRIMINAL PROCEEDINGS: A COMPARATIVE LEGAL ANALYSIS (World Conference on Social Sciences, Law and Public Policy, 2026)
The safety of participants in criminal proceedings has become a paramount concern across jurisdictions, especially in cases involving organized crime, terrorism, or vulnerable witnesses. While protective measures such as anonymity, witness relocation, and special interrogation techniques are essential, they often raise complex questions regarding the admissibility and reliability of evidence obtained under such circumstances. This article examines the legal standards and practices concerning the admissibility of evidence collected during protective procedures, with a focus on comparative developments in the United States, the United Kingdom, the European Union, and international criminal law. Through an analysis of landmark cases and legislative frameworks, the article identifies emerging trends, legal dilemmas, and potential safeguards to ensure both fair trial rights and the protection of justice system participants.
Keywords: Admissibility of evidence, Witness protection, Criminal proceedings, Fair trial, Confrontation rights, Anonymous witnesses, Special measures, Comparative criminal law, Human rights in criminal justice, Evidence and due process, International criminal law, Safety of participants, Procedural safeguards, Remote testimony, Judicial discretion